Are Firms Willing to Pay Lower Wages? A Quasi-Experiment on Subminimum Wage Policy - Petri Böckerman; Toni Juuti; Tuomas Kosonen; Henri Keränen (Institute of Labor Economics (IZA), 2024)
We examine a subminimum wage policy in the Finnish retail trade sector during 1993–1998 that allowed firms to pay subminimum wages to newly hired workers under the age of 25. This quasi-experiment enables us to compare wages for new hires in retail trade with those in similar industries. Despite the ongoing recession, the policy was adopted by firms sparingly, with most eligible workers being hired at the standard minimum wage. We propose that wage norm at the standard minimum wage creating indirect costs for firms paying subminimum wage would be the mechanism why the take-up of subminimum wage by firms remained low. We provide empirical evidence supporting this mechanism, most notably the excess mass at the standard minimum wage in the wage distribution of eligible workers. Many firms that paid the subminimum wage also reverted back to paying the standard minimum wages for subsequent hires.
Keywords: J31; J38; D22; 330; minimum wages; subminimum wage; wage determination; fairness; employment; firms